Avatars and Toolboxes: Digital Identity and Sense of Learning in High School Adolescents - Díaz-Barriga-Arceo, Frida (2020)
In this qualitative case study, a group of secondary school students, in a situation of academic vulnerability and social risk, were asked to develop two tasks to explore their identity as learners. The teenagers made digital infographics with an avatar (identity drawing) and a toolbox (cultural artifacts they use to learn), as well as a narrative that explains their meaning. The participants did not define themselves adolescents as problematic or with learning deficits, but they expressed a lack of motivation and inclination for school learning due to the curricular contents, the forms of teaching, and the management of school regulations. The types of learning that generate more sense and create identity symbols occur in relation to the youth media culture, as well in their communication and recreation practices in cyberspace. They do not report the link between formal and informal learning nor personalization of school learning activities, which hinders the construction of sense and meaning in school settings.